2016
DOI: 10.15713/ins.jmrps.43
|View full text |Cite
|
Sign up to set email alerts
|

Micronuclei as prognostic marker: A clinicopathologic study

Abstract: Background: Tobacco products attribute to oral cancer. Chronic smoking causes permanent damage to the oral mucosal cells and results in micronuclei (MN) formation. Aims and Objectives: The present study design was to assess the MN number in different locations of the oral cavity and to assess the damaging effects in patients who smoke and those who had left the habit recently. Materials and Methods:Three groups were included in the study. The first group included smokers; the second group included those who re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
(9 reference statements)
1
0
0
Order By: Relevance
“…The effects of DNA damage or chromosomal exposure on the basal cell turnover rate influence the peak expression and hence the optimal timing between 7 to 21 days after exposure is required. 9 Our study showed an increase in MN count among smokers compared to non-smokers, which is in accordance with the studies conducted by Motgi et al, 10 and Sherashiya et al 11 However, micronuclei were also observed in the cytological smears of seven non-smokers out of a total of 34 (about 20% of the sample).…”
Section: Discussionsupporting
confidence: 92%
“…The effects of DNA damage or chromosomal exposure on the basal cell turnover rate influence the peak expression and hence the optimal timing between 7 to 21 days after exposure is required. 9 Our study showed an increase in MN count among smokers compared to non-smokers, which is in accordance with the studies conducted by Motgi et al, 10 and Sherashiya et al 11 However, micronuclei were also observed in the cytological smears of seven non-smokers out of a total of 34 (about 20% of the sample).…”
Section: Discussionsupporting
confidence: 92%